Tetraploid embryonic stem cells can contribute to the development of chimeric fetuses and chimeric extraembryonic tissues - Bingqiang Wen (Nature Portfolio, 2017)
Abstract Our study examined the in vivo chimeric and survival capacities of chimeras created by injecting tetraploid embryonic stem cells (ESCs) expressing green fluorescent protein (GFP) into diploid embryos. At 3.5 days post-coitum (dpc) and 4.5 dpc, the tetraploid ESCs were able to contribute to the inner cell mass (ICM) just as diploid ESCs tagged with GFP. At 6.5 dpc, 8.0 dpc and 10.5 dpc, the tetraploid ESCs manifested in the same location as the diploid ESCs. The GFP cells in the extraembryonic tissues and fetuses of tetraploid ESC chimeras were tetraploid as determined by fluorescence activated cell sorting (FACS). Furthermore, tetraploid ESCs contributed to the development of the placenta, embryolemma and umbilical cord at 13.5 dpc and 16.5 dpc; however, very less GFP cells were found in the fetuses of tetraploid ESC chimeras. We further found that the proliferation of tetraploid ESCs was slower than that of diploid ESCs. In addition, the relative mRNA expression in the three germ layers and the trophoblast was abnormal in the EBs of tetraploid ESCs compared with diploid ESCs. In short, slower proliferation and abnormal differentiation potential of tetraploid ESCs might be two of the reasons for their poor survival and chimeric capacities.